1995
DOI: 10.2337/diab.44.7.824
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Immunochemical Advanced Glycosylation End Products Precedes and Correlates With Early Manifestations of Renal and Retinal Disease in Diabetes

Abstract: Elevated levels of advanced glycosylation end products (AGEs) have been found in multiple tissues in association with diabetic vascular complications and during the microalbuminuric phase of diabetic nephropathy. In this study, we have used an AGE-specific enzyme-linked immunosorbent assay (ELISA) to measure skin AGEs to determine whether elevated levels can be detected before the onset of overt microangiopathy. Subjects with type I diabetes (n = 48) were graded for the degree of nephropathy (normal [23], micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(117 citation statements)
references
References 18 publications
6
110
0
1
Order By: Relevance
“…In our study, creatinine levels were independently related to skin autofluorescence in diabetic patients. Renal dysfunction in diabetic patients, but also in euglycaemic patients, contributes to increased tissue AGE accumulation and to the development of cardiovascular complications in these patients [3,12,13]. Smoking, which is recognised as a source of oxidative stress in vivo [32], was also correlated with increased skin autofluorescence in control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, creatinine levels were independently related to skin autofluorescence in diabetic patients. Renal dysfunction in diabetic patients, but also in euglycaemic patients, contributes to increased tissue AGE accumulation and to the development of cardiovascular complications in these patients [3,12,13]. Smoking, which is recognised as a source of oxidative stress in vivo [32], was also correlated with increased skin autofluorescence in control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is limited by the fact that not all AGE exhibit fluorescent properties. ELISA-based assays have shown that increased accumulation of specific AGE occurs prior to increased autofluorescence in diabetes [12]. Fluorescence, as expressed in our autofluorescence ratio, is a group reactivity; consequently, it cannot provide quantitative information on the concentrations of individual compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Hammes et al [37] demonstrating, (i) the presence of AGE products in retinal capillaries of 26-week diabetic rats, and (ii) significant reduction in the number of diabetes-induced acellular capillaries and pericyte loss when the formation of AGE is inhibited with aminoguanidine, seems to suggest a possible link between excessive accumulation of AGE and the pathogenesis of diabetic retinopathy. There does appear to be a good correlation between the extent to which AGE accumulates on patients' dermal collagen and the degree of diabetic retinopathy [38]. More recently, Stitt et al [32] have demonstrated that AGE-modified albumin co-localizes with the p60 and p90 component of the AGE-receptors in the retinal vasculature of both diabetic rats and AGE-infused rats suggesting that progressive accumulation of AGE may well be the underlying mechanism for the loss of pericytes and endothelial cells in early diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetes, changes of colour perception are a feature of the onset of diabetes from its earliest pre-symptomatic onset [1,122]. This research suggests that, at least in the case of diabetes, such changes of colour perception are associated with the earliest onset of diabetes [123,124], the levels of insulin and/or blood glucose, and/or the production of highly bioluminescent glycated proteins [125,126].The development of type 2 diabetes is now measured by determining the levels of glycated haemoglobin although glycated insulin would appear to have been a more logical choice. Insulin has a relatively low half-life which may have made the selection of glycated insulin more problematic.…”
mentioning
confidence: 98%